EVALUASI PENERAPAN BUDAYA 5S ( SENYUM, SAPA, SALAM, SOPAN, DAN SANTUN ) DALAM KEPUASAN PASIEN RAWAT JALAN RUMAH SAKIT ISLAM METRO - Maya Aprilianingsih; Dita Tri Sekarwati (LPPM Universitas Awal Bros, 2026)
Outpatient services are one of the service units that greatly influence the hospital’s image and patient satisfaction. Based on the observation results, Rumah Sakit Islam Metro experienced a 15.72% decrease in patient visits. This decline was identified through reviews on Google Maps and direct observations, which showed that employees were still not optimal in implementing 5S behavior (Smile, Greeting, Salutation, Politeness, and Courtesy) in service delivery. The implementation of 5S culture has become essential as an effort to improve service quality and increase patient visits. This study aims to evaluate the consistency of 5S culture implementation on outpatient satisfaction at Rumah Sakit Islam Metro. Method used was descriptive qualitative with a case study approach, which seeks to understand phenomena occurring in the field through direct observation and focuses deeply on one object of study. Data were obtained through direct observation of employees, management, and outpatients visiting the hospital, followed by interviews based on questions prepared by the researcher. The results showed that the Standard Operating Procedure (SOP) of 5S culture had been implemented well by employees. Most patients stated that they were satisfied with the services provided, and this was proven by a 19.19% increase in patient visits. The conclusion of this study shows that the implementation of the 5S culture SOP plays an important role in improving service quality, patient satisfaction, and the number of outpatient visits. The 5S culture is an effective strategy in building patient trust and loyalty toward hospital services. Keywords: 5S SOP, outpatient services, patient visits, patient satisfaction, hospital.